Autoimmune diabetes in adults and risk of myocardial infarction: the HUNT study in Norway. (22nd July 2016) - Laugsand, L. E.; Janszky, I.; Vatten, L. J.; Dalen, H.; Midthjell, K.; Grill, V.; Carlsson, S.
Abstract: Background: The long‐term consequences of autoimmune diabetes in adults (AIDA) are largely unexplored. Objective: To investigate the risk of myocardial infarction (MI) in AIDA compared to type 2 diabetes, taking into consideration the effects of socio‐economic and lifestyle factors, the metabolic syndrome and glycaemic control. Methods: A total of 62 995 participants including 207 individuals with AIDA (onset ≥35 years and anti‐GAD positive) and 2322 individuals with type 2 diabetes (onset ≥35 years and anti‐GAD negative), from the population‐based Norwegian HUNT study, were followed for a first MI during the period 1995–2008. We identified 2614 MIs by hospital records or the National Cause of Death Registry. Cox proportional hazard models were used to estimate the risk of MI by diabetes subgroups after adjustment for age and socio‐economic and lifestyle factors. Results: AIDA amongst women was associated with a nearly fourfold increased risk of MI [hazard ratio (HR) 3.63, 95% confidence interval (CI) 2.21–5.96) compared to nondiabetic participants, whereas no excess risk was found in men with AIDA (HR 1.30, 95% CI 0.70–2.52). By contrast, type 2 diabetes was associated with an increased MI risk in both men (HR 1.92, 95% CI 1.62–2.26) and women (HR 2.39, 95% CI 1.98–2.89). The metabolic profile was more favourable in patients with AIDA than in those with type 2 diabetes, but glycaemic control was worse. Multivariable models and sensitivity analyses suggest that these results were robust. Conclusions: Women with AIDA were more likely to develop MI, compared to men with AIDA and both men and women with type 2 diabetes. Further investigations are warranted to confirm this gender difference.